TOAFL.com: A CEFR-Based Simulation Platform for Learning Al-Arabiyah Lil Akadimiyah Among Indonesian Students - Nanda Siska Safitri,; Mohammad Rofiqi,; Muhajir,; Boby Bagas Purnama,; Shosita Manrova, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to analyze the application of Toafl.com as a simulation platform for learning Al-Arabiyah lil Akadimiyah based on CEFR (Common European Framework of Reference for Languages) to support the Arabic language skills of students of the Interdisciplinary Islamic Studies Program (SII) Nahdlatul Ulama University (UNU) Yogyakarta. The research method uses a qualitative-descriptive approach with data collection techniques in the form of observation, interviews, and documentation for half a semester. The subjects of this study were class 3B students of the Interdisciplinary Islamic Studies Program (SII) UNU Yogyakarta. The results of the study indicate that the application of Toafl.com can help students understand question patterns, improve linguistic skills, and help students understand various Arabic language skills, including Istima' (listening), Kalam (speaking), Qira'ah (reading), and Kitabah (writing), according to the CEFR level (A1-C2). In addition, Toafl.com is also able to provide direct feedback, making it an effective tool in identifying weaknesses and potential improvements in students' Arabic language skills. This study recommends a wider integration of Toafl.com into the Arabic language learning curriculum at the college level.